Individual, Sexual, and Health Risk Factors Associated With HIV/AIDS Incidence - Setiawan, Luluk; Masrizal, Masrizal; Syafrawati, Syafrawati (JIK-JURNAL ILMU KESEHATAN, 2026)
Background: HIV/AIDS remains a major public health challenge in Indonesia. Dharmasraya Regency, West Sumatra, ranks second in HIV prevalence among districts in the province (0.018%), with cases increasing from 3 new infections in 2023 to 8 cases by October 2024. The specific pattern of risk factors driving this upward trend in Dharmasraya remains insufficiently documented.Objective: This study aimed to identify risk factors of individual characteristics, sexual behavior, and health history associated with HIV/AIDS incidence in Dharmasraya Regency.Methods: An analytical study using a non-matching case-control design was conducted from March to May 2025. A total of 117 participants were recruited from the HIV/AIDS Information System (SIHA 2.1): 39 laboratory-confirmed HIV-positive cases (total sampling) and 78 HIV-negative controls (systematic random sampling, 1:2 ratio). Data were collected through structured, interviewer-administered questionnaires. Bivariate analysis was performed using the Chi-Square test (α = 0.05), with crude odds ratios (OR) and 95% confidence intervals (CI) calculated for each variable.Results: Five variables were significantly associated with HIV incidence: risky sexual practices (OR = 44.24; 95% CI: 9.83–199.02; p < 0.001), non-heterosexual orientation history (OR = 5.57; 95% CI: 2.40–12.93; p < 0.001), history of sexually transmitted infections (OR = 5.47; 95% CI: 2.06–14.50; p = 0.001), family history of HIV/AIDS (OR = 5.33; 95% CI: 2.08–13.70; p = 0.001), and male gender (OR = 2.62; 95% CI: 1.12–6.09; p = 0.039). Age, education level, occupation, marital status, and condom use showed no statistically significant association.Conclusion: Risky sexual practices, non-heterosexual orientation history, STI history, family history of HIV/AIDS, and male gender are significant risk factors for HIV incidence in Dharmasraya Regency. Targeted prevention programs addressing behavioral risk factors and stigma-free healthcare access are urgently recommended. Future research should employ multivariate methods to identify independent risk factors.